Changing Concerns in Educational and Vocational Counseling - Woodsworth, J. G. (Canadian Journal of Counselling and Psychotherapy, 2012)
Technologically advanced nations have moved farenough into the post-industrial era so that they are now experiencing- strong so- cial pressures for greater flexibility in the formal education and career planning of both youth and adults. Such flexibility must take into account the life-long nature of educational processes and the changing nature of work. Accordingly, the vocational psychologist will need to re-examine his past pre-occupations in order to ascertain whether or not his models and empirical data are any longer relevant to the solution